UJI VALIDITAS DAN RELIABILITAS TES TEKNIK SHOOTING DAN LONG PASSING UNTUK PENYELEKSIAN PEMAIN SEPAKBOLA USIA 18 23 TAHUN - Achmad Widodo, (Arena, 2012)
ABSTRACT  This study aims to determine the validity and reliability of test shooting and long passing techniques in soccer players aged 18-23 years. Subjects in this study were members of the club football competition Gresik Regency Executive Branch, amounting to 50 players.Based on the results of research has been done, the validity  of test instruments shooting right and left foot with a distance of 23 meters, as well as passing the test instrument long right leg and left leg as far as distance is obtained by correlating the results of the first test and score a total of two tests. The results of the first test and the correlation between total scores showed that the level of shooting tests test the validity of the right foot for a perfect 0.94 in the category, and test instruments shooting the left leg of 0.89 with enough categories. While the long test instrument passing the right leg of 0.86 with the categories and test instruments long enough passing the left foot of 0.76 with the medium category. To test the validity of the technique of 0.89 with enough categories. While the degree of reliability is calculated by the method of re-test. The results of using the product moment correlation between the results of the first test with the second test to find the degree reliabiltas showed that the shooting test instrument reliability of 0.92 with the right foot perfectly categories, and test instruments shooting the left leg of 0.86 with a perfect category. While the long test instrument passing the right leg of 0.90 with a perfect category and test instruments left foot long passing of 0.81 with a perfect category. To test the technique with reliability of 0.95 with a perfect category.The conclusion of this study was shooting a test instrument with a distance of 23 m long test instruments and passing at a distance as far as possible, using tests the right leg and left leg has a level of validity and reliability is good. Based on these results that both supported by the results of test validity and reliability testing technique is good technique can also be said that both the test instrument is a good technique when used to perform the selection of players aged 18 -23 years.Keywords: Test Validity, Reliability, Shooting, Passing Long, 18-23 Players